2014
DOI: 10.1542/peds.2014-0639
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of a Parental Tobacco Control Intervention in Pediatric Practice

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Parental smoking cessation helps eliminate children' s exposure to tobacco smoke. A child' s visit to the doctor provides a teachable moment for parental smoking cessation. Effective strategies to help parents quit smoking are available for implementation.WHAT THIS STUDY ADDS: Evidence-based outpatient intervention for parents who smoke can be delivered successfully after the initial implementation. Maximizing parental quit rates in the pediatric context will require more complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…6 Pediatric primary care-based smoking cessation interventions can be effective in helping parents quit, but barriers have prevented further adoption and sustainability of such practices. [8][9][10] Time, recordkeeping challenges, logistical issues, scope of practice concerns, and lack of insurance reimbursement are cited as barriers to providing counseling and prescribing nicotine replacement therapy (NRT). 11,12 To address some of these concerns, professional organizations have adopted policy statements and clinical guidelines that underscore the importance of all clinicians addressing tobacco smoke exposure, including recommendations that pediatricians provide counseling and treatment to adults who expose their children to SHS.…”
mentioning
confidence: 99%
“…6 Pediatric primary care-based smoking cessation interventions can be effective in helping parents quit, but barriers have prevented further adoption and sustainability of such practices. [8][9][10] Time, recordkeeping challenges, logistical issues, scope of practice concerns, and lack of insurance reimbursement are cited as barriers to providing counseling and prescribing nicotine replacement therapy (NRT). 11,12 To address some of these concerns, professional organizations have adopted policy statements and clinical guidelines that underscore the importance of all clinicians addressing tobacco smoke exposure, including recommendations that pediatricians provide counseling and treatment to adults who expose their children to SHS.…”
mentioning
confidence: 99%
“…Pediatric-based smoking cessation interventions in a variety of care settings may be effective in helping parents quit, but barriers have prevented further adoption and sustainability of such practices [8][9][10]. Time, logistical issues, record-keeping challenges, scope of practice concerns, and lack of insurance reimbursement are cited as barriers to counseling and prescribing NRT [11].…”
Section: Introductionmentioning
confidence: 99%
“…Parents who smoke are receptive to receiving smoking cessation interventions when their child is hospitalized [7]. Inpatient pediatric clinicians, however, rarely provide such treatments to parents who smoke [7,8].Pediatric-based smoking cessation interventions in a variety of care settings may be effective in helping parents quit, but barriers have prevented further adoption and sustainability of such practices [8][9][10]. Time, logistical issues, record-keeping challenges, scope of practice concerns, and lack of insurance reimbursement are cited as barriers to counseling and prescribing NRT [11].…”
mentioning
confidence: 99%
“…In one randomized controlled trial, clinics trained to implement CEASE had significantly higher rates of quitline enrollment rates, smoking cessation medication provision, and counseling for smoking cessation, than clinics that were not receiving the CEASE intervention [8]. A follow-up study found that these clinics were able to sustain these effects over time after the official study had ended [10]. Although CEASE has been shown to be an effective intervention [8,10] the study included the first 22 practices that responded to the request to participate in the research study and the sample likely included clinics that were more motivated to implement the CEASE intervention.…”
Section: Introductionmentioning
confidence: 99%
“…A follow-up study found that these clinics were able to sustain these effects over time after the official study had ended [10]. Although CEASE has been shown to be an effective intervention [8,10] the study included the first 22 practices that responded to the request to participate in the research study and the sample likely included clinics that were more motivated to implement the CEASE intervention. A review of other interventions to address SHS found less promising results [11].…”
Section: Introductionmentioning
confidence: 99%